2020
DOI: 10.1177/0145482x19900715
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of General Self-Efficacy and Employment in Adults with Retinitis Pigmentosa

Abstract: Introduction: In this study, the author examined the association between general self-efficacy (GSE) and employment status in working-age adults with retinitis pigmentosa (RP; N = 183). The author further examined the associations between employment status and factors that were previously found to be linked to employment outcomes in individuals with visual impairments: educational attainment, mobility tool use (i.e., use of dog guide or cane), ability to drive, age, gender, and age at onset of visual impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…A recent study found that one of the most common causes of non-acceptance of assistive devices among people with visual impairments was social stigma and the fear of loss of employment, especially in working-age adults [ 52 ]. Similarly, another study exploring employment outcomes among adults with Retinitis Pigmentosa found that use of a cane or guide dog significantly reduced the odds of being employed among study participants [ 53 ]. These findings point to the fact that social acceptability towards aids and assistive devices is still low, especially for traditional or non-mainstream devices, and efforts are needed to change such attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that one of the most common causes of non-acceptance of assistive devices among people with visual impairments was social stigma and the fear of loss of employment, especially in working-age adults [ 52 ]. Similarly, another study exploring employment outcomes among adults with Retinitis Pigmentosa found that use of a cane or guide dog significantly reduced the odds of being employed among study participants [ 53 ]. These findings point to the fact that social acceptability towards aids and assistive devices is still low, especially for traditional or non-mainstream devices, and efforts are needed to change such attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations for VR counselors to screen employers’ organizational attitudes toward visual impairment were offered. Zapata 89 People with BVI with RP diagnosis; N = 183. Purposive sampling OS with measure; multiple logistical regression analysis Results indicated that individuals with RP who have elevated levels of Self-efficacy had higher odds of employment, while those who utilized a mobility tool had lower odds.…”
Section: Methodsmentioning
confidence: 99%
“…27,70,72,73,80 The severity of visual impairment (e.g., total/legal blindness, low vision) or fulfilment of certain criteria for low vision (e.g., the criteria for visual impairment by the International Classification of Diseases [ICD] or the WHO) was reported in the majority of studies. But only a few studies 74,[81][82][83][84][85][86] provided more information about the diagnoses of visually impaired participants. Some studies (42%) also reported additional disabilities (nonvisual), such as physical or mental disabilities.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%